Investigation of reactive power referring to recent studies of time-averaged stored energy density - Jiangwei Chen; Jiacheng Qiu (AIP Advances)
It is known that the energies associated with reactive power periodically exchange between power supply and energy storage component(s) of capacitor and/or inductor. However, reactive power may be altered by power electronic devices without capacitors or/and inductors, which cannot be reasonably explained following electrical power theory. In this work, the transmission, dissipation, and storage of electromagnetic energy of either a sinusoidal alternating current or an electromagnetic wave traveling in a transmission line are addressed; a positive definite expression of time-averaged stored energy density instead of the usual non-positive definite one is proposed. It is demonstrated that, under certain conditions, the product of voltage and current intensity may be applied to represent instantaneous power, and active power is consistent with dissipated energy. However, reactive power is related to part of stored energy, which indicates that reactive power relates to part of the energy exchange between the power supply and the considered circuit. Furthermore, it is shown that influences of thyristors on stored energy may be attributed to the change of (fundamental frequency) current intensity induced by the thyristor and the contribution of the resistor to stored energy, which may also alter the value of reactive power. This work may be helpful to establish a bridge between electrical power theory and Poynting’s theorem, deepen the understanding of reactive power, and improve electrical power theory.